The diaphragm as an anti-reflux barrier: A manometric, oesophagoscopic, and transmucosal potential study. Issue 6 (November 1972) - Habibulla, K. S.
Abstract : An infusion technique was used to measure pressures at the lower end of the oesophagus in normal patients and in those with hiatus hernia. These studies show a band of raised pressure at the lower end of the oesophagus in normal patients. This band was abnormally long in the majority of patients with hiatus hernia, but in others it resolved into two bands, particularly in patients with hiatus hernia and a short oesophagus. When the distance between these two bands was compared with the length of the oesophagogastric junction above the hiatus radiologically and at oesophagoscopy, a significant correlation was found. It, therefore, is postulated that one of these bands is produced by the inferior oesophageal sphincter and the other by the diaphragm, and thus it is demonstrated that the diaphragm must be included among the factors controlling reflux.